Production of polyclonal and monoclonal antibodies against CD54 molecules by intrasplenic immunization of plasmid DNA encoding CD54 protein - Moonsom S. (2014)
DNA immunization, in theory, is of great interest as a source of specific antibodies against different antigens. In an attempt to produce polyclonal and monoclonal antibodies against cell surface molecules by using the DNA immunization strategy, intramuscular and intrasplenic routes of DNA injection were compared. Two to five, but not a single, intramuscular DNA immunizations induced anti-CD54 and anti-CD147 antibody production. In contrast, a single intrasplenic immunization of CD54-encoding DNA could induce anti-CD54 antibody production. To produce monoclonal antibody (mAb), spleen cells obtained from an intrasplenic CD54-encoding DNA immunized mouse were fused with myeloma cells using the standard hybridoma technique. A hybridoma secreting specific mAb to CD54 was established. The generated mAb reacted to CD54 protein expressed on transfected COS cells and various cell types, the same as using standard CD54 mAb MEM-111. Our results demonstrated that direct immunization of antigen-encoding DNA into spleen is an effective route for production of both polyclonal and monoclonal antibodies to cell surface molecules. This finding is very useful for the production of antibodies to cell surface molecules where the protein antigen is not available or difficult to prepare, but cDNA encoding the corresponding protein is available.